Estimation of aircraft component production cost using knowledge based engineering techniques. Issue 3 (August 2015) - Zhao, Xiaojia; Verhagen, Wim J.C.; Curran, Richard
Abstract A comprehensive method is presented to estimate aircraft component production costs using Knowledge Based Engineering (KBE) techniques. A suite of parametrical cost estimation blocks are treated as Cost Primitives (CPs), which contain attributes such as cost types, cost driving parameters, and cost estimation relationships. A CP is associated with a parameterized geometry and a set of specific design parameters including part/assembly types, materials and production methods. Production cost is estimated by aggregating the cost of different CPs within a tree structure integrating both product breakdown and cost breakdown structures. The cost analysis tool is integrated into a KBE application by building Capability Modules (CMs), which provide manufacturable geometric representations for cost estimation and can be used to summarize output reports for further optimization. Case studies concerning stiffened panels are carried out, verifying the accuracy of the cost estimation method and illustrating the applicability of this method together with the integrated KBE application for various aircraft components. The main contribution of this research is automating the cost integration in the design process to improve the fidelity, repeatability and traceability of cost analysis.